2022
DOI: 10.3390/ijms232415734
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Migration of Mitochondria toward Cells and Tissues with Mitochondrial Damage

Abstract: Mitochondria are organelles that play a vital role in cellular survival by supplying ATP and metabolic substrates via oxidative phosphorylation and the Krebs cycle. Hence, mitochondrial dysfunction contributes to many human diseases, including metabolic syndromes, neurodegenerative diseases, cancer, and aging. Mitochondrial transfer between cells has been shown to occur naturally, and mitochondrial transplantation is beneficial for treating mitochondrial dysfunction. In this study, the migration of mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, the injection of autologous or non-autologous mitochondria has been effective in treating injury and various diseases [ 27 , 28 ], reviewed in [ 29 ]. In line with this, a recent paper has shown that exogenous healthy mitochondria are preferentially trafficked to cells and tissues in which mitochondria are damaged [ 30 ], which has implications for the delivery of therapeutic agents to injured or diseased sites. Whether this process happened after bariatric surgery needs further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the injection of autologous or non-autologous mitochondria has been effective in treating injury and various diseases [ 27 , 28 ], reviewed in [ 29 ]. In line with this, a recent paper has shown that exogenous healthy mitochondria are preferentially trafficked to cells and tissues in which mitochondria are damaged [ 30 ], which has implications for the delivery of therapeutic agents to injured or diseased sites. Whether this process happened after bariatric surgery needs further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Surely, an intriguing question pertains to the degree of cellular damage required to initiate the intercellular transfer of functional mitochondria. Although the underlying mechanisms of the migration of mitochondria toward cells and tissues with damaged mitochondria are not fully understood, the transfer of healthy mitochondria ameliorates mitochondrial defects and, above all, aids in the recovery of cellular function [191,[194][195][196][197]. Mitochondria transfer from mesenchymal stem cells not only structurally but also functionally repairs renal proximal tubular epithelial cells in diabetic nephropathy in vivo [198].…”
Section: Involvement Of the Mitochondria In Diseases Rare And Notmentioning
confidence: 99%
“…This method of fusing normal cells with mtDNA-deficient cells to form healthy hybrids compensates for mitochondrial dysfunction in mtDNA-deficient cells [222]. Lee et al observed in a co-culture model that exogenous mitochondria were preferentially transported to mitochondria-damaged cells and tissues, which has implications for the delivery of therapeutic agents to sites of injury or disease [223]. Shin and co-workers used a pig model to show that mitochondrial transplantation by intracoronary delivery in the heart is safe, has specific distribution to the heart, and leads to a significant increase in coronary blood flow [224].…”
Section: Mitochondrial Transplantationmentioning
confidence: 99%